Soy protein supplement intake for 12 months has no effect on sexual maturation and may improve nutritional status in pre‐pubertal children. (20th May 2018) - Duitama, Sandra M; Zurita, Javier; Cordoba, Diana; Duran, Paola; Ilag, Leopold; Mejia, Wilson
Abstract : Aim: To evaluate the intake of a soy protein‐based supplement (SPS) and its effects on the sexual maturation and nutritional status of prepubertal children who consumed it for a year. Methods: Healthy children ( n = 51) were recruited and randomly assigned to consume the lunch fruit juice with ( n = 29) or without ( n = 22) addition of 45 g of a commercial soy protein‐based supplement (SPS) over 12 months. Nutritional assessment including anthropometry (bodyweight, height, triceps skinfold thickness, mid‐upper arm circumference), body mass index (BMI), upper arm muscle area, arm muscle circumference, upper arm area, upper arm fat area data were derived from measures using usual procedures; age and gender‐specific percentiles were used as reference. Sexual maturation was measured by Tanner stage. Isoflavones were quantified using liquid chromatography and tandem mass spectrometry. Results: Height, BMI/age, weight/age and height/age were significantly different ( P < 0.05) at 12 months between girls in the control and intervention groups. Statistically significant differences between groups by gender ( P < 0.05) were found in boys in the control group for the triceps skinfold thickness and fat area. Nutritional status was adequate according to the World Health Organization parameters. On average, 0.130 mg/kg body weight/day of isoflavones were consumed by children, which did not show significant differences in their sexual maturation. Conclusion: Consumption of SPS for 12 months did not affect sexual maturation or the onset of puberty in prepubertal boys and girls; however, it may have induced an increase in height, BMI/age, height/age and weight/age of the girls, associated with variations in fat‐free mass.